Upaya Meningkatkan Hasil Belajar Siswa Melalui Penerapan Metode Integrated Curriculum Pada Siswa Kelas VII MTS Jam’iyah Mahmudiyah Tanjung Pura - Khuraina Ainal Qisti Dalimunthe; Muhizar Muchtar; Nurmisda Ramayani (Al-Tarbiyah : Jurnal Ilmu Pendidikan Islam, 2024)
From the explanation and research process carried out by the researcher, it is known that the Integrated Curriculum Method for class VII students at MTs Jam'iyah Mahmudiyah Tanjung Pura is very well implemented because it is able to improve learning outcomes. students who can be seen in the implementation of the second cycle. Students' understanding of learning is better with the implementation of the Integrated Curriculum method compared to the usual or conventional learning methods that have been applied so far. It can be concluded that the Integrated Curriculum method is effective. Efforts to improve student learning outcomes in learning moral aqidah in class VII MTs Jam'iyah Mahmudiyah Tanjung Pura were successfully carried out by implementing the Integrated Curriculum method in accordance with the plans that had been made. Efforts are made to actively involve students in every learning activity and explore students' potential so that students' creativity emerges. The increase in student learning outcomes by applying the Integrated Curriculum method is known through the student activity sheets that have been created and show good improvement through the application of the Integrated Curriculum method. Increasing student creativity in learning also influences student learning outcomes which also increase. In learning, students appear more active and enthusiastic in following the lesson material provided by the teacher in the learning process in class.